Myxozoan Diversity Infecting Ornamental Fishes Imported to Australia - Trujillo-González, Alejandro; Allas, Joshua; Miller, Terrence L.; Becker, Joy A.; Hutson, Kate S. (Frontiers in Marine Science, 2022)
The ornamental fish trade provides a pathway for the global translocation of aquatic parasites. Myxozoa is comprised of highly specialized metazoan parasites of aquatic hosts with a wide host range. Interest in the group has intensified along with the development of aquaculture due to emergent pathogenic myxozoan species in both freshwater and marine environments. However, little is known on myxozoan diversity in the ornamental fish trade. We examined 630 ornamental fish imported from Asia to Australia (representing 24 fish populations, including freshwater and wild caught marine fish species) for myxozoan parasites during 2015. Fish were sampled under Australian quarantine following veterinary certification that they showed no clinical signs of pests and diseases from the exporting country and visual inspection at Australian border control. Myxozoan parasites infected 8 of 12 freshwater populations and 8 of 12 marine fish populations. A total of 12 morphologically distinct Myxobolus spores were detected amongst all goldfish, Carassius auratus populations. Myxidium spores were detected in kissing gourami, Helostoma temminckii, and Ceratomyxa sp. spores were detected in cardinal fishes, Cheilodipterus quinquelineatus, Pterapogon kauderni, and Zoramia leptocantha. Kudoa sp. spores were detected in C. quinquelineatus, Sphaeramia nematoptera and Z. leptocantha. Results of this study show that Australian pre-export health requirements and visual inspections do not reliably detect myxozoan infections. Inspection prior to exportation and at border control should account for the highly cryptic nature of myxozoan parasites and consider alternative detection methods to complement inspections at border control.